2019
DOI: 10.1002/jctb.6109
|View full text |Cite
|
Sign up to set email alerts
|

Volume intensified dilution of a ring‐closing metathesis in ethyl acetate by means of a membrane‐assisted process in solvent recycle

Abstract: BACKGROUND Ring‐closing metathesis (RCM) for the synthesis of macrocycles has been used more and more often over recent years, including some interesting applications on industrial scale. However, like all macrocyclization strategies RCM is plagued by the traditional issue of low volume efficiency. To‐date this is typically addressed in a molecule specific manner with varying degrees of success. Here we report a process intensification method of metathesis macrocyclization that reduces the solvent load require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In addition, most nonalcoholic water-miscible solvents (e.g., 1,2-dimethoxyethane or 1,4-dioxane) are metal-coordinating and generally suppress metathesis. Informed by reports of conventional RCM in ethyl acetate as solvent, 35 we were pleased to discover methyl acetate as a much better solvent for both catalysts A and B (∼4 mM). When a methyl acetate/ethanol/water solvent mixture was used, fully homogeneous reaction mixtures were observed, even for solutions at high ionic strengths.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, most nonalcoholic water-miscible solvents (e.g., 1,2-dimethoxyethane or 1,4-dioxane) are metal-coordinating and generally suppress metathesis. Informed by reports of conventional RCM in ethyl acetate as solvent, 35 we were pleased to discover methyl acetate as a much better solvent for both catalysts A and B (∼4 mM). When a methyl acetate/ethanol/water solvent mixture was used, fully homogeneous reaction mixtures were observed, even for solutions at high ionic strengths.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Most notably, ethyl acetate, an environmentally friendly solvent, was the most privileged additive for this reaction. [14,15] Thus, we observed that molecules that can coordinate the empty coordination site 'activate' this catalyst for RCM. Reassessing the previous results (RCM only at the higher concentrations without additives), it seemed plausible to propose that the high concentration of the diester could be activating the catalyst by the same mechanism.…”
Section: Resultsmentioning
confidence: 84%